Mechanoelectrical transduction in chondrocytes. (19th February 2018) - Servin‐Vences, Martha Rocio; Richardson, Jessica; Lewin, Gary R; Poole, Kate
Summary: Cartilage tissue lines the joints of mammals, helping to lubricate joint movement and distribute mechanical loads. This tissue is comprised of isolated cells known as chondrocytes which are embedded in an extracellular matrix. Chondrocytes produce and maintain the cartilage by sensing and responding to changing mechanical loads. Mechanosensitive ion channels have been implicated in chondrocyte mechanotransduction and recent studies have shown that both PIEZO1 and TRPV4 can be activated by mechanical stimuli in these cells. The 2 channels mediate separate but overlapping mechanoelectrical transduction pathways, PIEZO1 in response to stretch and substrate deflections and TRPV4 in response to substrate deflections alone. These distinct pathways of mechanoelectrical transduction suggest a mechanism by which chondrocytes can distinguish between different stimuli that arise in their complex mechanical environment.